Shadow Children: Among the Brave - Book 5 - Haddix, Margaret Peterson (New York : Simon & Schuster Books for Young Readers, 2004)
In a society that allows families to have only two children, a group of third-borns tries to save itself and others like them.
"A shadow children book."
Keywords: Junior Fiction